Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12933-017-0615-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of empagliflozin on subclinical left ventricular dysfunctions and on the mechanisms involved in myocardial disease progression in type 2 diabetes: rationale and design of the EMPA-HEART trial

Abstract: BackgroundAsymptomatic left ventricular (LV) dysfunction is highly prevalent in type 2 diabetes patients. Unlike the other hypoglycemic drugs, SGLT2 inhibitors have shown potential benefits for reducing cardiovascular death and risk factors, aside from lowering plasma glucose levels. With this study we aim at determining whether the treatment with empagliflozin is associated with an improvement in LV functions in diabetic patients with asymptomatic LV dysfunction against Sitagliptin, which is presumably neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 69 publications
0
33
0
1
Order By: Relevance
“…31 Other RCTs investigating the effects of SGLT2i on LV remodelling in patients with T2D and HF are currently ongoing. 32,33 A RCT exploring cardiac effects of SGLT2i using impedance cardiography showed that 12 weeks of treatment with dapagliflozin had no significant effects on cardiodynamic parameters related to blood flow (stroke volume, cardiac output, cardiac index), systolic function (ejection fraction, acceleration and velocity indexes, systolic time ratio), circulatory function (systemic vascular resistance index), and fluid status (thoracic fluid content), compared to placebo. 34 Several possible mechanisms have been suggested to explain the beneficial effect of SGLT2i on cardiovascular outcomes, but not yet formally proven.…”
Section: Cardiac Effect and Cardiovascular Outcomesmentioning
confidence: 99%
“…31 Other RCTs investigating the effects of SGLT2i on LV remodelling in patients with T2D and HF are currently ongoing. 32,33 A RCT exploring cardiac effects of SGLT2i using impedance cardiography showed that 12 weeks of treatment with dapagliflozin had no significant effects on cardiodynamic parameters related to blood flow (stroke volume, cardiac output, cardiac index), systolic function (ejection fraction, acceleration and velocity indexes, systolic time ratio), circulatory function (systemic vascular resistance index), and fluid status (thoracic fluid content), compared to placebo. 34 Several possible mechanisms have been suggested to explain the beneficial effect of SGLT2i on cardiovascular outcomes, but not yet formally proven.…”
Section: Cardiac Effect and Cardiovascular Outcomesmentioning
confidence: 99%
“…Thus, GLS-guided management using antihyperglycemic drugs as well as cardioprotective drugs for DCM patients with T2DM at a given stage of HF, may be able to prevent progression to later HF stages and offer new insights into the management of DCM patients with T2DM. In fact, prospective studies are currently being conducted to examine the association of antihyperglycemic drugs such as sodium-glucose cotransporter 2 inhibitors or dipeptidyl peptidase-4 inhibitor with GLS in T2DM patients [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…There are currently ongoing clinical studies that are also utilizing cardiac magnetic resonance imaging to assess the effects of SGLT2 inhibitors on cardiac structure and function, as shown in Table . In addition, studies utilizing speckle‐tracking echocardiography for the measurement of global longitudinal strain and three‐dimensional echocardiography for more accurate quantification of LV structure in people with diabetes and normal LV ejection fraction are underway . Although these studies also involve a relatively small cohort of participants, they will be able to provide useful insights and hypotheses for further larger studies to be conducted in this area.…”
Section: The Effect Of Sodium‐glucose Cotransporter 2 Inhibitors On Lmentioning
confidence: 99%